Prison, punishment and penance in Late Antiquity - Hillner, Julia (Cambridge University Press, 2015)
"This book traces the long-term genesis of the sixth- century Roman legal penalty of forced monastic penance. The late antique evidence on this penal institution runs counter to a scholarly consensus that Roman legal principle did not acknowledge the use of corrective punitive confinement"--